Physicochemical Characterization and Evaluation of a Microemulsion System for Gamma-Linolenic Acid Methyl Ester. Issue 5 (3rd May 2016) - Li, Yi; Gao, Xiaoxi; Hou, Changmin; Yu, Kaifeng
Abstract : The purpose of this study was to investigate the possibility for parenteral delivery of Gamma-linolenic acid methyl ester without chemical modification using a microemulsion. Microemulsions composed of gamma-linolenic acid methyl ester and Tween 80 were prepared using PEG 400 as a cosurfactant. The effect of formulation variables on the particle size of the microemulsion was investigated. TEM image indicates the liquid droplets of the microemulsion are spheral shape. The mean droplet size of microemulsion system (Tween 80: GLA = 3:1) by PCS was about 50 nm and no changes were noted for at least six months.